2020
DOI: 10.1007/s00339-020-03865-z
|View full text |Cite
|
Sign up to set email alerts
|

Cations distribution by Rietveld refinement and magnetic properties of MgCrxFe2−xO4 spinel ferrites

Abstract: Magnesium-chromium ferrites MgCrxFe2−xO4 (0 ≤ x ≤ 1) were studied using X-ray diffraction and magnetization measurements. Rietveld refinement of XRD patterns confirmed the cubic spinel structure in the space group Fd-3m and enabled to obtain the cations' distribution amongst octahedral and tetrahedral sites of this structure. Magnetization measurements were performed using vibrating sample magnetometer (VSM) in the temperature range of 300-700 K and superconducting quantum interference device (SQUID) in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…ticles in each cluster, the minimization of the magnetic dead layer effect can be associated with the promotion of direct exchange and dipolar interactions that are described to minimize the decrease of the saturation magnetization [59]. Nonetheless, the inversion degree and inter-sublattice A-B super-exchange interaction were found to well describe the saturation magnetization dependence on the Ca/Mn ratio (see discussion and Figure S9A,B in Supplementary Material) [4,32,33,[60][61][62][63][64][65].…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…ticles in each cluster, the minimization of the magnetic dead layer effect can be associated with the promotion of direct exchange and dipolar interactions that are described to minimize the decrease of the saturation magnetization [59]. Nonetheless, the inversion degree and inter-sublattice A-B super-exchange interaction were found to well describe the saturation magnetization dependence on the Ca/Mn ratio (see discussion and Figure S9A,B in Supplementary Material) [4,32,33,[60][61][62][63][64][65].…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…Rietveld refined X-ray diffractograms of Co 0.9 Zn 0.2 Y x Fe 1.9-x O 4 nanoferrite samples are shown in Figure 1. All the XRD patterns were analyzed by the Rietveld refinement based programme FullProf [19]. The refinement was performed by using the initial input parameters of cubic symmetry with space group-Fd-3m and a pseudo-Voigt function as free parameter.…”
Section: X-ray Analysismentioning
confidence: 99%
“…Magnesium ferrite nanostructure is formed as inverse spinel structure (inversion degree of 0.9) where the octahedral sites in the crystallographic plane are occupied by both Fe 3+ and Mg 2+ ions (Manohar and Krishnamoorthi 2017;Wu et al 2018;Ivanets et al 2021a). The degree of inversion of magnesium ferrite crystals completely depends on the synthesis methods (Ouyahia et al 2020).…”
Section: I) Xrdmentioning
confidence: 99%
“…Tang et al (2013b) tested the iron and magnesium ratio from 90:10 to 10:90 and found that increasing magnesium content shifted the XRD peaks toward lower angle positions. Further modification of magnesium ferrites through doping with other elements directly affects the crystallite structure which will appear on the XRD spectra (Ouyahia et al 2020). Interestingly XRD diffraction patterns of MgFe 2 O 4 are very similar with those of γ-Fe 2 O 3 , which requires further analysis such as SEM-EDS, ICP-MS and XPS for differentiation of these two crystals (Tang et al 2013b).…”
Section: I) Xrdmentioning
confidence: 99%